Enterprise Risk Management In Banking Industry - Christina Liem (President University, 2018)
Enterprise Risk Management (ERM) in banking industry is a rare topic in academic research, even though ERM implementation becomes new regulation from the banking regulators since year 2014. The purpose of this study is to examine ERM implementation during the early stage of the ERM implementation regulation in Indonesian, especially its impact towards bank performance and vice versa. This study focuses on all 4 (four) state-owned commercial banks in Indonesia though a descriptive explanatory study and data panel GLS simple regression by STATA MP-64. This study employs ERM Index (Gordon et al, 2009) as a proxy of ERM implementation; and bank performance is presented by 3 (three) proxies: NIM, ROAA, and EM. The findings show that 75% of state-owned commercial banks have positive ERM Index, and also, they have the different maturity stage of ERM implementation. Moreover, this study identifies that ERM Index has positive significant impact towards ROAA and vice versa; ERM Index has positive but insignificant impact towards NIM and vice versa; and ERM index has positive but insignificant impact towards EM. As a conclusion, this study proposes to all commercial banks in Indonesia should implement ERM seriously implement because it has been proven that ERM implementation delivers positive impact towards bank profitability and it transmits a positive signal to shareholders.